Projekt badawczy tekstu staro-cerkiewno-słowiańskiego ewangeliarza krótkiego - Ostapczuk, Jerzy (Slavistica Vilnensis, 2010)
The article represents a short description of the Research Project focused on the Old Church Slavonic Gospel Text preserved in abbreviated Gospel lectionary manuscripts. The importance of the lectionaries in Greek and Slavonic traditions is shown in a short introduction, the state of research of Greek gospel lectionaries is analysed as well. The article explains the main purposes and methodology of the Project described. The first step is to collate Gospel readings (starting from the beginning of the Lectionary) in all abbreviated Gospel Lectionary manuscripts (fragments which could have been originally part of this Aprakos type will be included too). No longer unit for a collation will be concerned, than the individual Gospel lection. Compared in this way, the text will give an opportunity to research the history of the Church Slavonic Gospel Lectionary and its text, text critics, theory of translation, vocabulary, etc. The collated text could also be compared with the Greek New Testament critical editions. The collation of the liturgical Gospel reading from the Gospel of John (3,16–21) for the second Tuesday after the Resurrection, based on 14 manuscripts, is given as an example.